2020
DOI: 10.1002/lipd.12222
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Fat Oxidation during Submaximal Exercise in Sedentary Persons: Variations by Medium‐Chain Fatty Acid Composition and Age Group

Abstract: Previous studies in recreational and trained athletes aged mostly in their 20s have reported that short‐term ingestion of medium‐chain triacylglycerols (MCT) enhances fat oxidation (FAO) during submaximal exercise. However, whether the FAO‐enhancing effect of MCT with a different composition of medium‐chain fatty acids (MCFA) occurs in older sedentary persons is unclear. The present study investigated the effect of MCT ingestion with different proportions of MCFA in sedentary participants in their 40's and 50'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…However, there are many issues to be considered, including the fact that continuing a high-fat diet is detrimental because it involves a drastic change in diet, and even if it can be continued, it will increase body weight and body fat, which is concerning [ 30 ]. On the other hand, it has been shown that the application of 6 g of MCTs per day causes increased fat burning in skeletal muscle even in those on a normal fat diet, with or without exercise habits [ 10 , 11 , 12 ]. Furthermore, this study showed that a continuous ingestion of only 2 g of MCTs per day can enhance fat burning during low-intensity physical activity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, there are many issues to be considered, including the fact that continuing a high-fat diet is detrimental because it involves a drastic change in diet, and even if it can be continued, it will increase body weight and body fat, which is concerning [ 30 ]. On the other hand, it has been shown that the application of 6 g of MCTs per day causes increased fat burning in skeletal muscle even in those on a normal fat diet, with or without exercise habits [ 10 , 11 , 12 ]. Furthermore, this study showed that a continuous ingestion of only 2 g of MCTs per day can enhance fat burning during low-intensity physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the mean difference and standard deviation of the cumulative fat oxidation and the maximum fat oxidation rate during low-intensity physical activity after ingestion of 6 g of MCTs for 2 weeks compared with the control [ 11 ], the number of subjects required for the study was estimated to be 18 or more and 23 or more. While the ingested amount of MCTs was one-third of that in the estimated study, a highly sensitive mass spectrometer was used to measure oxygen uptake and carbon dioxide production, which are the basic values for calculating fat oxidation, so the required number of subjects was judged to be slightly higher than the estimated number, 27 subjects were set, and so the target number of subjects was set at 30, based on the expectation that 10% of the subjects would be ineligible for analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…MCFAs induce much greater increase in the activity of the muscle oxidative enzyme (Montgomery et al, 2019) (Thevenet et al, 2016). A study carried out with sedentary individuals in the age group 40 and 60 years who received a diet rich in medium-chain fatty acids showed that exercising increases and improves the aerobic capacity in terms of oxygen transport and cardiac output capacity (Nosaka et al, 2020).…”
Section: Medium-chain Fatty Acid In Lipid Oxidationmentioning
confidence: 99%